Effect of admixing CU and sintering parameters on the densification and mechanical properties of microwave sintered 316L stainless steel - Ching Chin Ho (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
In this research, researching the effect of Cu to the sintering parameter on the densification and mechanical properties of using microwave sinterd the 316L stainless steel. The variable parameter in this research are the sintering temperature, heating rate and the enviroment when sintering. The enviroment of sintering either is gas nitrogen or gases argon. The sample will sintering in the 2.45GHz microwave sintering furnace. The randomized block is use to analysis the best parameter to the sintering process on same material.